The role of inducible Nitric Oxide Synthase in teeth periapical lesions immunopathogenesis caused by Enterococcus faecalis - Tamara Yuanita; Latief Mooduto; Kuntaman Kuntaman (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Periapical lesions, are characterized by an immune response to the invading bacteria consequences periapical bone destruction. In root canal treatment failure was found Enterococcus faecalis (E. faecalis) as most species. iNOS found an important role in protection against infection, plays vital roles in fighting pathogens and contributing to disease pathology. Purpose: This study was to observed the role of iNOS in teeth periapical lessions immunopathogenesis caused by E. faecalis. Methods: The randomized post-only control group design used in this study, This study used 24 Wistar rats, were divided into three groups (each group consisted of 8 rats), as negative controls group is a normal teeth, in the positive controls group was made by drilling the upper right first molar to penetrate the dental pulp and was induced with 10µl BHI-b then filled with Glass Ionomer Cement (GIC) and the treatment group, after drilling the teeth, then inoculated with E. faecalis ATCC 29212 106 CFU into 10µl BHI-b then filled with GIC to prevent contamination. It takes 21 days to get periapical lesions and rat were sacrificed, and then the expression of iNOS was measured. Results: Statistical analysis using ANOVA found a significant differenced between control and treatment groups (p<0.05). Conclusion: This study concluded that iNOS role in teeth periapical lesions immunopathogenesis caused by E. faecalis.Latar belakang: Lesi periapikal merupakan hasil suatu respon imun untuk melawan invasi bakteri yang mengakibatkan destruksi tulang periapikal. Pada perawatan saluran akar yang mengalami kegagalan ditemukan Enterococcus faecalis sebagai spesies terbanyak. iNOS berperan penting untuk proteksi terhadap bakteri, mempunyai peran yang vital untuk melawan patogen dan berkonstribusi secara patologik untuk menyebabkan suatu penyakit. Tujuan: Penelitian ini bertujuan untuk mengobservasi peran iNOS secara imunohistokimia pada lesi periapikal tikus Wistar. Metode: Penelitian ini menggunakan disain randomized post-only control group, digunakan 24 ekor tikus Wistar yang dibagi menjadi tiga kelompok yang masing-masing terdiri dari 8 ekor tikus, sebagai kelompok kontrol negatif adalah gigi normal, pada kelompok kontrol positif dilakukan pengeboran pada gigi molar pertama rahang atas sampai menembus pulpa kemudian diinduksi 10µl BHI-b kemudian ditumpat (Glass Ionomer Cement) GIC dan pada kelompok perlakuan, setelah dilakukan pengeboran dilakukan induksi E. faecalis ATCC 29212 sebanyak 106 CFU ke dalam 10 µl BHI-b kemudian ditumpat GIC untuk mencegah kontaminasi. Diperlukan waktu 21 hari untuk mendapatkan lesi periapikal pasca perlakuan kemudian tikus dikorbankan lalu dihitung sel-sel yang mengekspresikan iNOS. Hasil: Analisis menggunakan ANAVA membuktikan bahwa ada perbedaan yang bermakna antara kelompok kontrol dan kelompok perlakuan (p<0,05). Kesimpulan: iNOS berperan pada imunopatogenesis lesi periapikal gigi akibat E. faecalis.